La parole comme soin : cancer et pluralisme thérapeutique - Ilario Rossi (Anthropologie & Santé)
When facing cancer, every sick person is confronted in one way or another with the bio-medical field, which marks his or her own perception of disease. Therefore, the recourse to other possible therapies must be understood through the person’s experience; his choices and reasons relate as much about his view of others therapies as about his perceptions of allopathic answers. In order to better appreciate the issues of supply and demand, we have to recognize the background in which this logic is built. By referring to the case of Switzerland, the purpose of this paper is to understand the notion of choice through the concept of “capability” applied to the field of health. This pluralism will be studied with the help of different actors’ stories. More specifically, reconsidering the concept of « speech », we will focus on what it conveys as action, between saying and doing. Thus, the various conceptions of « care », their specificities, their finalities will be set in dialogue. This illustrative overview is intended to link the various « speeches » of therapists with the conceptions of « care » that are sustained by patients. Finally, it will be possible to understand therapeutical pluralism as a social process which, for every sick person, links physical experimentation and individual’s emergence as a process, which promotes the development of a cultural strategy against the uncertainty caused by the disease.